Epidemiology of Rotavirus diarrhea in children under five: A hospital-based surveillance in Jakarta - Muzal Kadim; Yati Soenarto; Badriul Hegar; Agus Firmansyah (Indonesian Pediatric Society Publishing House, 2011)
Background Rotavirus is still a major cause of acute diarrhea in children around the world, both in developed and developing countries. WHO Surveillance from 2001 to 2008 showed that in children under five years of age treated for acute diarrhea, on average 40% of cases were caused by rotavirus. A previous study in Indonesia showed that the incidence of rotavirus diarrhea in children ranged from 20%􀁑60% of diarrhea cases. However, there have been few studies identifying the genotypes of rotavirus strains in Indonesia. This infonnation is indispensable for manufacturing vaccines. Objective To examine the epidemiology of rotavirus diarrhea, including genotypes and clinical characteristics, in children under five years who were hospitalized in Jakarta. Methods This study was a prospective surveillance conducted at Cipto Mangunkusumo Hospital, Jakarta from January to December 2007 investigating hospitalized children under five years of age who suffered from acute diarrhea. Results Ninety􀁑nine patients joined the study. The incidence of rotavirus infection in this study was 67%. The youngest was 2 months of age and the oldest 54 months of age, Mth an average age of 13.6 months. As much as 92% of rota virus diarrhea was found in subjects aged 3􀁑23 months, Mth a peak age of 12􀁑23 months. Nutritional status, degree of dehydration, bloating, fever, blood in stool, and mucus in the feces were not significantly different between rotavirus and non􀁑rotavirus diarrhea. Vomiting tended to be more frequently experienced by children Mth rotavirus diarrhea than those with non􀁑rotavirus (88% vs. 67%). There was no clear, seasonal pattern for rotavirus diarrhea. Most G genotypes in this study were G1 (35%), G9 (12.5%), G2 (7.5%) and the majority of P genotypes were P6 (52.5%), P8 (17.5%) and P4 (10%). Conclusions The incidence of rotavirus diarrhea in hospitalized children under five years of age in Jakarta was 67%, with a predominance ofG1, G9 and G2 genotypes.